A jackhammer in the gullet: high amplitude oesophageal contractions as a cause of atypical chest pain. (5th October 2015) - Goel, Rishi; Anggiansah, Angela; Wong, Terry; Wilkinson, Mark
Abstract : Chest pain is a common cause for referral to emergency departments. A proportion of these patients have non-cardiac chest pains with normal investigations. Such patients should be considered for oesophageal studies as these may reveal an underlying dysmotility disorder. We report the case of a 51-year-old man who presented with chest pain and underwent oesophageal studies. He was diagnosed with acid reflux and high amplitude oesophageal contractions, otherwise known as a jackhammer oesophagus. Treatment was successful with omeprazole and glyceryl trinitrate relieving his symptoms.